ASSOCIATION BETWEEN HUSBAND SUPPORT WITH EXCLUSIVE BREASTFEEDING MOTHER TO CHILD AGE 7-12 MONTHS - srimiyati, srimiyati (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Exclusive breastfeeding is the best nutrition for infants during the first six months of life for healthy growth and development. However, the prevalence of exclusive breastfeeding is very low in many developing countries including Indonesia. Breastfeeding is an important public health strategy for improving the health of children and mothers. The success or failure of breastfeeding is largely dependent on the availability of assistance and support. The purpose of this study was to investigate the relationship between husband's support for exclusive breastfeeding mothers to Child age 7-12 months. The research quantitative, design applies cross sectional. The sample of this study is mothers who have child age 7-12 months. The sample size was 71 people, selected using accidental sampling. The collection data is questionnaire 3 types, instrument A for the respondent's characteristic, instrument B contain 20 support statements of husband and instrument C the statement of whether the mother gives exclusive breastfeeding. Data were analyzed by univariate and bivariate using chi square test and Fisher test. The result of this research very positive relationship between husband support and exclusive breast feeding (p = 0,017). Keywords: husbands support, exclusive breastfeeding.